2020
DOI: 10.3892/mco.2020.2077
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of bupivacaine on patient-derived sarcoma cells

Abstract: Sarcomas are rare tumors with limited treatment options. Although chemotherapy is standard for certain subtypes, overall survival has not improved in several decades. Bupivacaine has been shown to induce apoptosis and prevent cell growth in multiple different types of malignancies but has not been studied in sarcoma. The current study evaluated the effects of bupivacaine on multiple patient-derived sarcoma cells and a commercial sarcoma cell line. Multiple patient-derived sarcoma cell subtypes and a commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recently, several works have described the adjuvant anticancer action of local anesthetics such as LDC [19,20], bupivacaine [21][22][23][24] and ropivacaine [25]. LDC can suppress cancer cell growth (in vitro and in vivo) through several mechanisms: regulation of epigenetic changes, promotion of pro-apoptotic pathways and regulation of ABC transporters, also preventing metastasis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works have described the adjuvant anticancer action of local anesthetics such as LDC [19,20], bupivacaine [21][22][23][24] and ropivacaine [25]. LDC can suppress cancer cell growth (in vitro and in vivo) through several mechanisms: regulation of epigenetic changes, promotion of pro-apoptotic pathways and regulation of ABC transporters, also preventing metastasis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Certain anesthetics have been found to have antitumor activities ( 12 , 13 ), with effects on the apoptosis, proliferation, motility and drug resistance of various cancer cells. For example, one study demonstrated that clinically relevant concentrations of bupivacaine induced the apoptosis of sarcoma cells in vitro and suppressed their proliferation ( 14 ), and another study revealed that dibucaine had a pro-apoptotic effect on HL-60 promyelocytic leukemia cells ( 15 ). However, few studies have focused on the potential antitumor effects of lidocaine in glioma treatment.…”
Section: Introductionmentioning
confidence: 99%